Investigation into CME Shock Speed Resulting from Type II Solar Radio Bursts - Pauzi, F.A.M. (Springer, 2020)
An investigation into Type II solar radio bursts was carried out to understand the frequency gap between fundamental and harmonic emissions of the radio burst. This investigation focused on Type II solar radio bursts with flares and coronal mass ejections by relating the separation between fundamental and harmonic emissions. We used the Compound Astronomical Low-cost Low-frequency Instrument for Spectroscopy and Transportable Spectrometers (CALLISTO) and a newly designed low-frequency antenna array. This article describes the proposed new instrument in terms of its antenna design, the bandpass testing of the antenna, the new system significance in studying Type II solar radio bursts, and its comparison with other leading radio solar monitoring instruments. Upon setting up the new technology, the radio-frequency interference of the observation site at the University of Malaya was shown to emphasize the suitability of the selected site. This article also shows the preliminary results of the proposed new instrument by reporting the detection of a Type III solar radio burst that was confirmed by CALLISTO. Moreover, it also includes the optimal observation design and strategies for future detections. © 2020, Springer Nature B.V.